The Effect of Customer Perception, Brand Image, and Product Quality on Purchase Decisions of AQUA Bottled Water Among Customers in Medan City - Willy Sanjaya; Ferry Hidayat; Feriani Astusti Tarigan (International Journal of Business and Quality Research, 2026)
Purchase decisions for AQUA bottled water have experienced a decline due to customerperceptions, brand image, and product quality, which have not yet reached optimal levels. Thepurpose of this study is to identify and analyze the influence of customer perceptions, BrandImage, and Product Quality on the Purchase Decision of AQUA bottled water among customersin Medan. This research utilizes a descriptive quantitative method. Primary data were collectedthrough questionnaires and interviews. The population consists of AQUA customers in Medan,with a sample size of 150 respondents determined using the Hair formula. The samplingtechnique employed was accidental sampling. Data analysis was conducted using multiplelinear regression analysis with SPSS version 27. The results indicate that customer perceptions,Brand Image, and Product Quality each have a significant partial effect on purchase decisions.Furthermore, the simultaneous analysis shows that customer perceptions Brand Image, andProduct Quality collectively influence the Purc hase Decision of AQUA bottled water amongcustomers in Medan.